4- Identity issues in urban ethno-communal con! ict in Africa: an empirical study of Ife-Modakeke crisis in Nigeria - Asiyanbola , Raimi Abidemi (African Sociological Review, 2009)
This paper examines identity issues in urban ethno-communal con" ict focusing on the case of Ife-Modakeke in Nigeria. ! e data used in the study is from a larger survey carried out by the author in Ife and Modakeke communities. ! e data collected was analysed using simple frequencies, percentages and correlation statistical technique. Given the circumstance that led to the birth of Modakeke; the status of Modakeke and that of its people has always been a source of dispute and con" ict. First, is the issue of landlord/tenant relationship and second, is the issue of indigene/non-indigene status and by extension the problem of citizenship. In both communities ethnic attachment is high, and, inter-personal relationship among the people in the two communities is not that very cordial. Signi# cant negative relationship is found between inter-personal relationship and age, age of the youngest child, and if most important organization belonged to is ethnic organization. Signi# cant positive relationship is found between inter-personal relationship and having relative in the other community (Ife or Modakeke). the result of the correlation analysis between ethnic attachment and inter-personal relationships among the people of the two communities though found not to be signi# cant shows a negative relationship. this result suggests that for sustainable peace to be attained there is the need to pursue policies that encourages social integration, as well as policies that discourage strong ethnic attachment and the spread of ethnically related organizations in the two communities.